PENIGKATAN KEMAMPUAN KOGNITIF BELAJAR ANAK MELALUI FLIP CHART - Eka Poppi Hutami; Yusannang Yusannang (Jurnal Panrita, 2022)
This study aims to determine how to increase the learning ability of children in the B3 group Raudhatul Athfal Addariyah DDI Palopo City. The type of research used is Classroom Action Research, with two cycles, namely the first cycle consisting of 3 meetings and the second cycle consisting of 3 meetings. The subjects of this study were the children of Group B1 Raudhatul Athfal Addariyah DDI Palopo for the academic year 2020/2021, totaling 24 children, consisting of 9 boys and 15 girls. The problem-solving method used is to apply the teaching and learning process by using flip charts to improve children's cognitive learning abilities obtained from observation interviews and documentation. The data of this study were analyzed descriptively and qualitatively. The success of this study is determined by the child getting a score. The results of this study indicate an increase in children's learning outcomes. The average score in the initial or pre-action conditions is 32% of all indicators and does not meet the good category. Cycle I with an average observation score of 62% of all indicators and has not met the good category. Cycle II with an average score of 92% overall from all indicators and reached good category. Thus, classroom action research (CAR) is said to be successful, so the research recommends learning using flip charts to improve the cognitive learning abilities of children in group B1 Raudhatul Athfal Addariyah DDI Palopo